2021
DOI: 10.1088/1361-6641/abeb84
|View full text |Cite
|
Sign up to set email alerts
|

Organic passivation of Al0.5Ga0.5N epilayers using self-assembled monolayer of Zn(II) porphyrin for improved solar-blind photodetector performance

Abstract: We report on the passivation of surface states of Al0.5Ga0.5N epilayers by employing self-assembled monolayers (SAM) of organic molecules, which led to a significant improvement in the performance of Al0.5Ga0.5N based solar-blind photodetector. The formation of SAM of meso-(5-hydroxyphenyl)-10,15,20-tri(p-tolyl) porphyrin (ZnTPP(OH)) on the surface of Al0.5Ga0.5N was probed by contact angle measurement (CA), X-ray photoelectron spectroscopy (XPS), and atomic force microscopy (AFM). The successful passivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To investigate the wavelength selectivity of the PDs, the response of the devices was studied by varying the incident wavelength over a broad range from 700 nm (visible) to 200 nm (deep UV). The responsivity is an important performance parameter of the PD and is mathematically given by , where P λ is the incident optical power corresponding to the wavelength λ. As shown in the inset of Figure b, all of the PDs were not responsive from 700 nm (visible) to 260 nm (UV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the wavelength selectivity of the PDs, the response of the devices was studied by varying the incident wavelength over a broad range from 700 nm (visible) to 200 nm (deep UV). The responsivity is an important performance parameter of the PD and is mathematically given by , where P λ is the incident optical power corresponding to the wavelength λ. As shown in the inset of Figure b, all of the PDs were not responsive from 700 nm (visible) to 260 nm (UV).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the wavelength selectivity of the PDs, the response of the devices was studied by varying the incident wavelength over a broad range from 700 nm (visible) to 200 nm (deep UV). The responsivity is an important performance parameter of the PD and is mathematically given by 44,45 = −…”
Section: Resultsmentioning
confidence: 99%
“…The device exhibited an even higher EQE of 28% under 10 V bias together with a highly suppressed dark current value of <0.2 pA at a higher bias of 20 V. Here, the high temperature AlN buffer plays an important role of high energy barrier, restricting the lateral flow of the leakage current in the device, which resulted in an ultra-low dark current density and a high performance large-area PD. In a recent work, Kaushik et al 52 investigated a surface passivation method, where the performance of an SB PD was further improved by employing self-assembled monolayers of organic molecules on the surface of an Al 0.5 Ga 0.5 N-based device structure. This surface passivated device yielded a significant reduction in the dark current, which led to ∼10 times improvement in its specific detectivity, hence improving the overall performance of the SB UVPD.…”
Section: Algan Materialsmentioning
confidence: 99%
“…Moreover, the GaSe akes were mechanically exfoliated, and it has been reported that akes obtained by mechanical exfoliation are prone to edge defects, which serve as traps to the photogenerated electron-hole pairs and reduce the overall speed of the fabricated device. 36,54,55 We further carried out KPFM measurements on the vertical GaSe/Si p-n heterostructure to understand its band alignment. KPFM is one of the electrical modes of AFM; it is used to obtain workfunction values and information regarding the surface potential and charge at the nanoscale.…”
Section: Papermentioning
confidence: 99%